Japan : Economic and Policy Developments. (IMF Staff Country Reports; Country Report ;, 1997)
This paper reviews economic and policy developments in Japan during the 1990s. It suggests that, while growth is likely to be adversely affected in the near term owing to the fiscal consolidation measures adopted as part of the FY1997 budget, the prospects are favorable for continued economic recovery, supported by improved labor market developments and external demand. A declining working-age population, however, will constrain underlying growth over the longer term. The paper also suggests that a deeper and more accelerated fiscal adjustment would help ensure a declining debt ratio over the medium term.